1997
DOI: 10.1093/ptj/77.12.1682
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Positioning and Exercise on Intracranial Pressure in a Neurosurgical Intensive Care Unit

Abstract: Physical therapy can be used safely in patients with normal or increased ICP provided that Valsalva-like maneuvers are avoided. [Brimioulle S, Moraine J-J, Norrenberg D, Kahn RJ. Effects of positioning and exercise on intracranial pressure in a neurosurgical intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
3
3

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 3 publications
4
48
3
3
Order By: Relevance
“…The variables assessed to evaluate the integrity of dynamic cerebral autoregulation-the LF gain between BP and CBFV oscillations and the phase shift between BP and CBFV oscillations-demonstrated that dynamic cerebral autoregulation remained stable during increasing levels of physical exercise despite the autonomic, mechanical, and metabolic effects of increasing physical effort (7,15,24,28,32,35,41,50,53). In our study, not only did the absolute gain remain stable but we also observed no change in normalized LF gain value.…”
Section: Discussionsupporting
confidence: 42%
“…The variables assessed to evaluate the integrity of dynamic cerebral autoregulation-the LF gain between BP and CBFV oscillations and the phase shift between BP and CBFV oscillations-demonstrated that dynamic cerebral autoregulation remained stable during increasing levels of physical exercise despite the autonomic, mechanical, and metabolic effects of increasing physical effort (7,15,24,28,32,35,41,50,53). In our study, not only did the absolute gain remain stable but we also observed no change in normalized LF gain value.…”
Section: Discussionsupporting
confidence: 42%
“…[1][2][3][4][5] Improved cardiopulmonary function, functional independence, and psychological well-being, as well as decreased length of stay, have been associated with early mobilization in the ICU. 1,[6][7][8] The negative effects of inactivity, such as increased depression, lack of coordination, decreased muscle strength, altered balance, and decreased cardiovascular and respiratory status, have also been well established in the literature for a variety of populations within acute care settings. 1,[6][7][8] The use of an external ventricular drain (EVD) to manage intracranial pressure (ICP) dates back to 1850 and is the most common neurosurgical procedure in North America; an estimated 20,000 are performed each year in the United States alone.…”
mentioning
confidence: 99%
“…1,[6][7][8] The negative effects of inactivity, such as increased depression, lack of coordination, decreased muscle strength, altered balance, and decreased cardiovascular and respiratory status, have also been well established in the literature for a variety of populations within acute care settings. 1,[6][7][8] The use of an external ventricular drain (EVD) to manage intracranial pressure (ICP) dates back to 1850 and is the most common neurosurgical procedure in North America; an estimated 20,000 are performed each year in the United States alone. 9-11 (Canadian statistics for this procedure have not been identified in the literature.)…”
mentioning
confidence: 99%
“…Exitem poucos trabalhos na literatura que avaliam esse assunto, porém todos acharam que a fisioterapia causa pequeno e temporário aumento da PIC, sem alteração de PPC. Portanto, as manobras de fisioterapia podem ser aplicadas em pacientes com TCE com segurança [15][16][17][18] .…”
Section: Resultsunclassified